IMPLEMENTASI KEBIJAKAN SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (STUDI PADA DINAS PEMBERDAYAAN MASYARAKAT, DESA DAN TRANSMIGRASI PROVINSI LAMPUNG) - Agus Purnomo; Suparti Suparti (Universitas Bandar Lampung (UBL), 2022)
The implementation of the Government Agencies Performance Accountability System policy appears to organize a clean and accountable government that is free of Collusion, Corruption, and Nepotism. In addition, as a public display of performance accountability. The problems in this study are: (1) Implementation of the Performance Accountability System Policy of Government Agencies at the Department of Community Empowerment, Villages and Transmigration of Lampung Province (2) Aspects that hinder and support the implementation of the Performance Accountability System Policy of Government Agencies (at the Department of Community Empowerment, Village and Transmigration Lampung Province)This researcher uses qualitative research methods, due to the current situation systematically. The research design used was a direct interview. Where this research design is carried out in-depth about the situation in the field based on facts, as well as looking at the relationship between variables and supporting variables.According to the results of the study, the lack of communication and the quality of human resources is an inhibiting factor in the Implementation of the Performance Accountability System Policy of Government Agencies. Budget and disposition are supporting factors in the implementation of the Performance Accountability System Policy of Government Agencies at the Department of Community Empowerment, Villages, and Transmigration of Lampung Province.